The Right to Health: COVID-19 Pandemic and the Opportunity to Transform Mental Health Inequalities in Indonesia - Anindyajati, Gina; Mardiasmo, Diashati Ramadhani; Sekarasih, Laras; Susilaradeya, Damar; Takwin, Bagus; Pelupessy, Dicky C.; Diatri, Hervita (Frontiers in Public Health, 2022)
The COVID-19 pandemic has caused major catastrophes worldwide. In Indonesia, the pandemic has caused greater barriers for individuals to access mental health services. This article aims to capture the state of public mental health in Indonesia using data from various national surveys. Four main problems were identified: the increase in depression, loneliness, and distress in the general population, disruption in accessing mental health services, mental health problems among vulnerable populations, and the limited scope of available mental health services and facilities in the community. This article provided practical recommendations for the Indonesian government that focuses on preparing a resilient mental healthcare system for future crises, reducing barriers to access mental health services, and expanding the available resources and programs to ensure equal and sustainable access to mental health services in the community.